EVALUATION OF THE LEVEL OF CONTAMINATION WITH PHTHALATES IN DAIRY PRODUCTS FOUND ON THE ROMANIAN MARKET - FĂT, Alina Ioana; MIHAIU, Romolica; KOVÁCS, Melinda Haydee; ROMAN, Cecilia; KOVÁCS, Emőke Dalma; NIKOLAOU, Filippos Georgios; VESA, Gabriela Valentina; TĂBĂRAN, Alexandra; DAN, Sorin Daniel; MIHAIU, Marian (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Human exposure to phthalates (artificial phthalic acid esters) is ubiquitous because of the widespread use of these chemicals in consumer and industrial products. The aim of this study was to determine the presence and amount of the phthalates in milk and dairy products collected in Romania. Samples were gathered at several stages during the production, primary production (farm), milk collection center and retail level. Six types of phthalates were assessed by gas chromatography with mass spectrum detection (GC-MS, of which only 4 were detected in the samples - di-n-butyl phthalate (DBP), di-2-ethylhexyl phthalate (DEHP), di-n-octyl phthalate (DOP) and dibutylbenzyl phthalate (BBP). The obtained concentrations ranged between 0.060 – 0.298 mg/kg for DEHP, in raw milk samples and 0.038 - 0.173 mg/kg respectively, in commercial milk. DMP and DEP were not detected in any sample. The lowest quantity of phthalates was detected in yogurt with 0.1% fat – 0.042 mg/kg, and the largest amount was recorded in butter with 75% fat – 0.683 mg/kg. The level of total phthalates in all samples analysed did not exceed the maximum permitted limit of 60 mg/kg.